Differences in Active Ingredients of White Chicory Leaves (Brassica pekinensis L) as a Bio-Larvicidal Against Aedes aegypti larvae - Marlik, Marlik; Okta, Dhea Stya; Ngadino, Ngadino; Nurmayanti, Demes; Sulistio, Irwan; Prasetyo, Aries (UI Scholars Hub, 2024)
Continuous chemical dengue control can cause vector resistance and environmental pollution. Developing natural larvicides (bio-larvicides) from plant toxins like white chicory, which can poison Aedes aegypti larvae, is necessary for a sustainable alternative. This study aimed to analyze differences in active ingredients in white chicory leaves (Brassica pekinensis L) as bio-larvicide against Aedes aegypti larvae. This study was a pure experiment using a post-test-only control design using 1,225 Aedes aegypti instar III larvae with extracts of alkaloid active ingredients, flavonoids, and concentrations of 0%, 24%, 34%, and 40% with 3 times replication. Data were analyzed using a probit test, one-way ANOVA, and Post Hoc LSD. The results showed the potential of active ingredients in white chicory leaves against the death of Aedes aegypti larvae (p-value = 0.000). The average percentage of larval mortality concentration was 24%, 34%, 40%, in alkaloids was 41%, 60%, 66%, and in flavonoids was 45%, 64%, 68%. The active ingredient of white chicory leaves can kill Aedes aegypti larvae with LC50 in 29% alkaloids and 27% flavonoids.